Conflict of Laws Relating to Marriage, Adoption, Surrogacy, and Custody of Children - Yadav, Deepanshu (International Journal of Law, Human Rights and Constitutional Studies, 2023)
The conflict of laws, also known as private international law, is a multifaceted legal field that addresses jurisdictional and choice of law conflicts arising from the interaction of different legal systems. This comprehensive review explores the intricate landscape of the conflict of laws as it relates to marriage, adoption, surrogacy, and child custody, focusing on the foundational principles, key issues, and evolving challenges in these areas. The review begins by elucidating the foundational principles of the conflict of laws, emphasizing the critical distinction between jurisdiction and choice of law. It proceeds to delve into the realm of marriage, examining how conflicts can arise in recognition, validity, and divorce of international marriages, with a special focus on the complex issues surrounding same-sex marriage. The subsequent section scrutinizes adoption and its intersection with the conflict of laws, especially in the context of inter-country adoption. It illuminates the challenges of eligibility criteria, legal processes, and the recognition of international adoptions. Surrogacy, as an increasingly prevalent global phenomenon, receives extensive attention in the review's third section. It elucidates the complexities of commercial versus altruistic surrogacy, parentage, citizenship, and cross-border medical issues. The fourth section deals with child custody disputes that transcend international boundaries, emphasizing the significance of jurisdiction, recognition, and the Hague Abduction Convention in ensuring the best interests of the child. In conclusion, the review underscores the evolving nature of the conflict of laws in a world characterized by increased global mobility and diversity. It emphasizes the need for ongoing collaboration between legal professionals, policymakers, and scholars to address the intricate legal and ethical challenges inherent in these vital aspects of family law, ultimately aiming to protect the rights and welfare of all parties involved.